Análisis de los instrumentos comunicacionales de posicionamiento y gestión de marca de la Prefectura de Los Ríos - Lage Rivera, Genesis Jomira (2020)
In recent years communication tools have become a mixture of communication tools implemented in marketing and a graphic design, which allows managing the positioning of a brand or image of a specific institution or company, in order to project it and dominate it in the minds of its consumers. In addition to promoting corporate communication, through internal and external communication that possess tangible and intangible resources. This research used as techniques the observation, interview and focus group, based on the collection of qualitative data to show that the communication tools used by the Prefecture of Los Ríos, which generate trust in the public are social networks such as Facebook, Twitter, Instagram, etc., in addition to promoting its promotional or advertising actions through its visual image within the local territory. Therefore, it has become a primary tool for the institutional identity itself that is generated when people know how to differentiate the institutional brand by their social work or the importance it has in a local framework, generating local difference and competitiveness obtaining long-term results. term, aiming to be perceived from beginning to end.